2020
DOI: 10.1111/ijac.13541
|View full text |Cite
|
Sign up to set email alerts
|

Phase and microstructural evolution of BaZrO3‐CaZrO3 refractory and its interaction with titanium alloy melt

Abstract: In this study, the effect of CaZrO3 additives on the phase and microstructure of BaZrO3 refractory were investigated as well as the interaction with titanium alloy melts. Results revealed that no second phase was observed in the BaZrO3 refractory with 10 and 20 mol% CaZrO3 additives, respectively, and the incorporation CaZrO3 additives promoted the densification and the growth of grains due to the generation of BaZrO3‐CaZrO3 solid solutions. Whereas, the appearance of CaZrO3 phase was in the BaZrO3 refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…In our previous study it was noted that CaZrO 3 was undergoed a limited solid solution reaction with BaZrO 3 . 21 Thus, both the CaZrO 3 and Ba 1-x CaxZrO 3 phases were present in the B3 crucible, due to the excess of CaZrO 3 . According to Equations 1 and 2, the absence of the Ba 1-x Ca x ZrO 3 phase in the B1 and B2 crucible might be attributed to the low precursor CaO content, which caused the less CaZrO 3 to be involved in the reaction to obtain less Ba 1-x Ca x ZrO 3 phase.…”
Section: Phase Constitution and Microstructure Of The Fused Bazro 3 D...mentioning
confidence: 98%
“…In our previous study it was noted that CaZrO 3 was undergoed a limited solid solution reaction with BaZrO 3 . 21 Thus, both the CaZrO 3 and Ba 1-x CaxZrO 3 phases were present in the B3 crucible, due to the excess of CaZrO 3 . According to Equations 1 and 2, the absence of the Ba 1-x Ca x ZrO 3 phase in the B1 and B2 crucible might be attributed to the low precursor CaO content, which caused the less CaZrO 3 to be involved in the reaction to obtain less Ba 1-x Ca x ZrO 3 phase.…”
Section: Phase Constitution and Microstructure Of The Fused Bazro 3 D...mentioning
confidence: 98%
“…Цирконат барію BaZrO 3 хоч і показує гарну інертність до титанових розплавів, але має незадовільні технологічні властивості, тому може використовуватися лише з добавками інших вогнетривів. В [23] спробували поліпшити характеристики вогнетриву BaZrO 3 шляхом додавання CaZrO 3 . При цьому введення добавок CaZrO 3 у кількості 10 і 20 мол.% сприяло ущільненню та росту зерен завдяки утворенню твердих розчинів BaZrO 3 -CaZrO 3 .…”
Section: проблеми технології формиunclassified
“…[39][40][41][42][43][44] For Ti 3 AlC 2 materials, it was reported that an appropriate amount of assistants (such as Si, Sn, and Nb) played a positive role in improving the purity and enhanced properties (hardness, strength, oxidation resistance, etc.). [45][46][47][48][49][50][51][52][53] For example, Ai et al 45 pointed out that the addition of Sn could extend the range of synthesis temperature and inhibit the forming of TiC and other impurities in the synthesis process of Ti 3 AlC 2 ceramic by preventing the generation of thermal explosion. Huang et al 46 reported that flexural strengths of Ti 3 Al 0.8 Sn 0.2 C 2 and Ti 3 Al 0.6 Sn 0.4 C 2 solid solution improved when compared with pure Ti 3 AlC 2 , which was a result of solid solution strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction would lead to a hardened generated layer on the metal surface, thereby affecting the performance of the metal. According to the chemical inertness of ceramics, many researchers [52][53][54][55][56][57][58][59] investigated the interaction between Tibased alloy with BaZrO 3 , CaZrO 3 , CaO, and so on. In addition, Cheng et al 60 proposed TiAlO-based refractories, a system containing Ti and Al, for the investment casting of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation